The bZIP1 Transcription Factor Regulates Lipid Remodeling and Contributes to ER Stress Management in Chlamydomonas reinhardtii. Issue 5 (20th March 2019) - Yamaoka, Yasuyo; Shin, Seungjun; Choi, Bae Young; Kim, Hanul; Jang, Sunghoon; Kajikawa, Masataka; Yamano, Takashi; Kong, Fantao; Légeret, Bertrand; Fukuzawa, Hideya; Li-Beisson, Yonghua; Lee, Youngsook
Abstract : The mRNA of a Chlamydomonas bZIP transcription factor is spliced by CrIRE1 under ER stress, and the resulting protein protects Chlamydomonas cells from ER stress by modulating lipid remodeling. Abstract: Endoplasmic reticulum (ER) stress is caused by the stress-induced accumulation of unfolded proteins in the ER. Here, we identified proteins and lipids that function downstream of the ER stress sensor INOSITOL-REQUIRING ENZYME1 (CrIRE1) that contributes to ER stress tolerance in Chlamydomonas ( Chlamydomonas reinhardtii ). Treatment with the ER stress inducer tunicamycin resulted in the splicing of a 32-nucleotide fragment of a basic leucine zipper 1 (bZIP1) transcription factor ( CrbZIP1 ) mRNA by CrIRE1 that, in turn, resulted in the loss of the transmembrane domain in CrbZIP1, and the translocation of CrbZIP1 from the ER to the nucleus. Mutants deficient in CrbZIP1 failed to induce the expression of the unfolded protein response genes and grew poorly under ER stress. Levels of diacylglyceryltrimethylhomoserine (DGTS) and pinolenic acid (18:3Δ5, 9, 12) increased in the parental strains but decreased in the crbzip1 mutants under ER stress. A yeast one-hybrid assay revealed that CrbZIP1 activated the expression of enzymes catalyzing the biosynthesis of DGTS and pinolenic acid. Moreover, two lines harboring independent mutant alleles of Chlamydomonas desaturase ( CrDES ) failed to synthesize pinolenic acid and were more sensitive to ER stress than were their parental lines. Together, these results indicate that CrbZIP1 is a critical component of the ER stress response mediated by CrIRE1 in Chlamydomonas that acts via lipid remodeling.